Learning quality factors associated with students' literacy and numeracy competencies: a systematic literature review - Yayat Suryatna; Widodo Widodo; Merry Lapasau; Oom Rohmah Syamsudin (Lentera Negeri, 2026)
The low literacy and numeracy competence of Indonesian students is a serious concern, as reflected in the 2022 PISA score, which is still below the international average. Learning quality is a key factor suspected to significantly influence the development of these two basic competencies. This study aims to systematically analyze the influence of learning quality on improving literacy and numeracy competencies based on empirical literature studies. The research uses the Systematic Literature Review (SLR) approach with the PRISMA protocol. Literature searches were conducted on indexed databases (Scopus, ERIC, SINTA, Google Scholar) with keywords related to learning quality, literacy, and numeracy. Of the 896 initial articles, 38 met the inclusion criteria for further analysis. The analysis shows that the quality of learning has a significant influence on literacy and numeracy competence through various dimensions: (1) the quality of teacher-student interaction and relational-intentional pedagogy; (2) teachers' competence in compiling HOTS and AKM-based questions; (3) the implementation of the independent curriculum and contextual approach; (4) the use of innovative technology and learning media; (5) learning environment at home and school; and (6) teacher training and professional development. Optimizing learning quality through a holistic approach that includes improving teachers' pedagogic competence, strengthening the literacy-numeracy-based curriculum, and integrating technology has proven effective in improving students' literacy and numeracy competencies. This study recommends sustainable policies for teacher professional development and improvement of learning infrastructure.